The impact of financial inclusion on mental health - Joseph B. Ajefu; Ayse Demir; Houra Haghpanahan (Elsevier, 2020)
This paper examines the impact of financial inclusion on the mental health of heads of household in Nigeria. The study employed data from the 2015/2016 Nigerian General Household Survey (GHS), matched with georeferenced data concerning financial services obtained from the Insight2Impact (i2i) GIS interface. The results indicate that financial inclusion has a strong positive impact on mental health. The study used a robust instrumental variable method, in which a household's distance from the nearest financial institution was used as the instrument for financial inclusion. In addition, it identified the potential channels through which financial inclusion can influence mental health, including: (1) food expenditure; (2) remittances; and (3) risk-coping mechanisms. The findings of this study reinforce growing evidence for the benefits of financial inclusion for alleviating depression symptoms.